Stormwater management : the study of rainwater harvesting system (Case Study of Zoo Negara) - Mohammed Yusof, Siti Aminah; Tukiman, Izawati (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This paper focuses on the operation of rainwater harvesting in Zoo Negara, Malaysia. It is to identify whether the system operates well or not. It also discusses about storm water management in Zoo Negara. The issues raised on the study are water management, scarcity of clean water supply, operational cost and water distribution into sewer system. The aim of this paper is to study the operation of rainwater harvesting in Zoo Negara. The objectives of the research are to understand how rainwater harvesting system utilized, identify the impact of rainwater harvesting and investigate better ways to operate the system in Zoo Negara. The methods used to collect data are observation and interview. Some pictures and videos were taken and analysed. Calls and emails contributed in data collection. The finding of the study is that the rainwater harvesting system in Zoo Negara is effective. The rainwater harvesting operated by NAHRIM is working properly because the water quality of Tunku Abdul Rahman Lake has improved. The conclusion is rainwater harvesting system in Zoo Negara is working properly but still can be improved in certain aspect.